Sustainable Resource Management: What, What For And How? - Singh, Ram Bali (National Geographical Journal of India, 2022)
As many as 8 goals of The 2030 Agenda, one way or the other, lay emphasis on sustainable management and utilization of resources. The 17 goals of the Agenda use the term ‘sustainable’ as many as 14 times and the word ‘inclusive’ 6 times As such the process of resource management needs to ensure sustainability, equity and inclusion. Resource management is a process of decision making regarding the allocation of resources based on survey, planning and implementation activities. It needs to resolve property conflict, development conflict and resource conflict in order to be economically viable, socially equitable and environmentally bearable. The idea of sustainable resource management takes in to consideration the concept of ‘needs’ and the idea of ‘limitations’ and emphasizes the need for equity and growth in a long term perspective. National governments and international organizations are actively engaged in developing location specific, cost effective, efficient and eco-friendly technologies of resource utilization, exploration, management and conservation. The paper examines the concept of resource scarcity, availability and abundance, discusses the rationale behind sustainable resource management and outlines an approach to achieve it.